Two-dimensional semiconducting Lu2CT2 (T = F, OH) MXene with low work function and high carrier mobility. Issue 6 (29th January 2020) - Bai, Xiaojing; Zha, Xian-Hu; Qiao, Yingjie; Qiu, Nianxiang; Zhang, Yiming; Luo, Kan; He, Jian; Li, Qiuwu; Huang, Qing; Francisco, Joseph S.; Lin, Cheng-Te; Du, Shiyu
Abstract : Potential structures for Lu-Based MXenes. Abstract : As a new family of two-dimensional materials, MXenes have attracted increasing attention in recent years due to their widespread potential applications. In contrast to early transition metals in convention, here we expand the M element of MXene to the rare earth element lutetium. Based on the first-principles density functional calculations, the bare lutetium-based carbide MXene Lu2 C is determined to be stabilized in the T-type configuration. Furthermore, both fluorine and hydroxyl terminated configurations are found to be semiconductors, and their band gaps are suitable for use in semiconductors and visible and near-infrared optical devices. The Lu2 C(OH)2 configuration shows a direct band gap and possesses an ultralow work function of 1.4 eV. Both Lu2 CT2 (T = F, OH) MXenes exhibit high carrier mobilities. Particularly, the electron mobility of the Lu2 C(OH)2 MXene is found to be anisotropic at room temperature, with values as high as 95.19 × 10 3 and 217.1 × 10 3 cm 2 V −1 ·s −1 in the zigzag and armchair directions, respectively, which makes Lu2 C(OH)2 a promising material for nanodevices. Based on these predicted properties, our work widens the range of MXene materials and their applications in semiconducting devices.